Efeito do congelamento prévio à maturação na qualidade da carne de bovinos Nelore e F1 (Nelore x Simental) terminados a pasto e confinado - Paula, Maria do Livramento de (2013)
This study aimed to evaluate genetic groups effects (GG; Bos indicus and Bos taurus), termination systems (TS; pasture and confined) and treatment prior maturation (TM; cold and frozen) on meat quality. It was utilized Longissimus thoracis muscle showcases of B. indicus (Nellore, n = 66), and B. taurus (Simmental x Nellore, n = 62), slaughtered with a carcass average weight between 264 and 305kg and age of 24 to 28 months. It was used the completely randomized delineation, in a 2 x 2 x 2 x 4 factorial arrangement, involving: 2 genetic groups (Nellore and F1 Nellore x Simmental) x 2 termination systems, intensive (confined) and extensive (pasture) x 2 conservation systems (cold and frozen) and 4 maturation time (MT; 0, 7, 14 and 21 days). Regarding the pH there was a significant interaction effect (p<0.05) of the maturation time involving genetic group and conservation system. On water-holding capacity there was an isolated effect (P=0.0084) of the termination system. There was a significant interaction (P=0.0737) with GG and TM for freezing effect. Cooking loss (22.67 and 31.07%) was unmodified by the studied genotypes. It was not observed any significant interaction or isolated effect (p<0.05) for total and insoluble collagen. For myofibrillar fragmentation index significant effect for genetic group (P=0.0210) and time of maturation (P=0.0031), shear force for time of maturation and termination system (P0=0.0001). Lightness (L*) significant interaction (P=0.0010) between GG, TS and TM, with lighter (31.31 ± 3.57) samples of frozen treatment than cold samples (30.24 ± 4.18). There was a significant interaction (P=0.0010) between TS and TM for redness (a*) and between GG and ST (P=0.0019) and GG and TM (P=0.0212) for yellowness (b*). There was significant difference (p<0.05) in GG, TS, TM and MT interaction and in SC and GG interaction for tenderness and overall impression (OI), with frozen meat being softer than the cold samples. For tenderness, was a significant interaction between the factors ST and TM (p <0.05) and between ST and MT (p <0.05) from the 14th day of meat aging. There was also significant interaction (p <0.05) between the factors in GG TM significant difference. At day 21 aging, meat of animals B. taurus were slightly softer than B. indicus.